The studio - Alberro, Alexander; Allen, Jennifer; Hoffmann, Jens, 1972-; Whitechapel Art Gallery (London : Whitechapel Gallery ; Cambridge, Massachusetts : The MIT Press, 2012)
Vito Acconci; Edgar Arceneaux; Art & Language; Atlier Lieshout; Francis Bacon; Louise Bourgeois; Constantin Brancusi; Marcel Duchamp; Jack Goldstein; Eva Hesse; Carsten Höller; Robert Irwin; Seydou Keita; Martin Kippenberger; Edward Krasinski; Laboratoire Agit-Art; Paul McCarthy; Takashi Murakami; Bruce Nauman;Mike Nelso; Gabriel Orozco; Martha Rosler; Dieter Roth; Carolee Schneemann; Robert Smithson; Wolfgang Tillmans; Richard Venlet; Ian Wallace; Andy Warhol; Lawrence Weiner; Francesca Woodman
"Co-published by Whitechapel Gallery and The MIT Press"--T.p. verso.
Formerly CIP.
boek
Keywords: Artists' studios